Intento de suicidio en adolescentes y adultos jóvenes desde una perspectiva fenomenológico-existencial (2019)
The purpose of this article is to contrast the logotherapeutic theory with the factors associated with suicidal behavior in adolescents and young adults, from a phenomenological-existential perspective. Based on the results of empirical studies on suicidal behavior, the findings related to the high-risk factors in this type of population are retaken, which is characterized by the immaturity of the life cycle within contexts that favor or put on high risk the development of identity as a person. Factors such as family, psychological, psychiatric and interpersonal are taken up in this article to understand from a logotherapeutic perspective the phenomenological field of suicidal behavior, likewise, from the theoretical elements will be an understanding of the loss of meaning of life as a cause of the suicidal behavior of the adolescent and the young adult.